Study of difference in child rearing practice based on sex of child among married women of reproductive age group in urban slum of Mumbai - Bedre, Rahul C.; Giri, Purushottam A.; Bote, Mangala M. (International Journal of Research in Medical Sciences, 2017)
Background: India a vast country has left behind a number of stigmas and prejudices to move ahead as one nation. Still in a number of states, villages, cities and towns, gender bias is persistent leading to female discrimination. Objective: To study the difference in child rearing practices based on sex of child among married women of reproductive age group in urban slum of Mumbai. Methods:A community based, cross-sectional study was carried out among 900 married women of reproductive age group during a period of Jan. 2007 to Jan. 2008 at Shivajinagar urban health centre, which is field practice area of T. N. medical college, Mumbai. Participants were selected by systematic random sampling in an urban slum of Mumbai, Maharashtra. Results:In present study, a total of 900 married women with their children below five year are 1158 (male: 632 & female: 526) were analyzed. There was statistically significant difference between child rearing practices like breast feeding initiation, complimentary feeding, immunization status, nutritional status, and treatment seeking behavior. Conclusion:The findings in the present study confirm that sex based difference in child rearing practices persist in urban slum area of Mumbai.